Influence of Urban Development on Extreme Precipitation in Plateau Lake Basin - LI Baofen; LI Xiaopeng; CAO Yimei; JIN Zhuo (Renmin Zhujiang)
Studying the influence of urban development on extreme precipitation in the lake basin region is of practical significance for urban flood control and disaster reduction,forecasting and early warning capability increase and emergency response capacity building,“four pres” improvement,and risk tackling of extreme precipitation and waterlogging disasters.Taking Kunming,a city in the Yunnan Plateau Basin,as an example,this paper adopts mathematical statistical methods to analyze the effect of urban development on the extreme precipitation index in the central urban area of the lake basin,the basin edges,and peripheral hilly areas of the city.The results show that urban development exerts different degrees of influence on various extreme precipitation indexes in lake basin areas,basin edges,and peripheral hilly areas of the basin, with the strongest,weakest,and middle effects on the basin edges, hilly areas,and lake basin areas respectively.Due to topography and the urban heat island effect,urban development also causes uneven increase and decrease in the extreme precipitation index in various areas such as lake basin areas,basin edges,and hilly areas.